PENGARUH MOTIVASI, KOMUNIKASI INTERPERSONAL DAN PENGHARGAAN TERHADAP KINERJA PEGAWAI PADA UPT SINGOSARI MALANG - Antonius Andrias Reis Tanesi (Accounting UNIPA - Jurnal Akuntansi, 2026)
The Job Training Unit (UPT-PK) Singosari serves as a technical implementation unit responsible for developing a skilled, knowledgeable, and professionally oriented workforce for the industrial sector. This study aims to: (1) describe the variables of motivation, interpersonal communication, rewards, and employee performance at UPT-PK Singosari; (2) analyze the effects of motivation, interpersonal communication, and rewards on employee performance; and (3) determine the dominant variable influencing employee performance. This study adopts an explanatory research approach using survey techniques, with a total of 59 employees serving as respondents. The research instrument, in the form of a questionnaire, was tested for validity and reliability. Data were analyzed using descriptive analysis, multiple linear regression, classical assumption tests, and hypothesis testing. The findings indicate that: (1) motivation, interpersonal communication, and rewards have a positive and significant effect on employee performance at UPT-PK Singosari; (2) motivation is the dominant factor influencing employee performance. These results suggest that enhancing intrinsic and extrinsic motivation is crucial for optimizing human resource productivity within technical training environments.